To convert the given equation from point-slope form (y - y1 = m(x - x1)) to slope-intercept form (y = mx + b), you need to manipulate the equation to isolate y on one side.
Given equation: y - 4 = (2/3)(3x + 6)
Distribute the (2/3) to both terms inside the parentheses:
y - 4 = (2/3)(3x) + (2/3)(6)
Simplify:
y - 4 = 2x + 4
Add 4 to both sides to isolate y:
y = 2x + 8
So the equation in slope-intercept form is y = 2x + 8.
which slope intercept form equation to the point slope equation y-4=2/3(3x+6)
1 answer